2006
DOI: 10.1007/s00125-006-0407-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved motor development and good long-term glycaemic control with sulfonylurea treatment in a patient with the syndrome of intermediate developmental delay, early-onset generalised epilepsy and neonatal diabetes associated with the V59M mutation in the KCNJ11 gene

Abstract: Aims/hypothesis Activating mutations in the KCNJ11 gene encoding the Kir6.2 subunit of the K ATP channels in pancreatic beta cells are a common cause of neonatal diabetes. One-third of patients also have developmental delay, which probably results from mutated K ATP channels in muscle, nerve and brain. Sulfonylureas, which bind to the sulfonylurea receptor 1 subunit of the K ATP channel, can replace insulin injections in patients with KCNJ11 mutations. The aim of this study was to investigate the long-term out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 22 publications
6
84
3
1
Order By: Relevance
“…The effectiveness of oral sulfonylurea in improving glycemic control of diabetic patients due to KCNJ11 mutations after transfer from insulin therapy has been confi rmed by many reports, with doses ranging from 0.05 to 1.5 mg/kg/d (12)(13)(14)(15)(16)(17); however data concerning the use of sulfonylurea in the treatment of PNDM with DEND syndrome have shown variable results. Several mutations related to severe DEND syndrome (Q52R, G53R, V59G, I296L, G334D) are insensitive to glibenclamide (4,12,19,20); nevertheless in some forms of intermediate DEND syndrome (I167L, G53D, H46L, V59M), characterized by less severe developmental delay and without epilepsy, glibenclamide therapy has improved metabolic control, neuromuscular symptoms (17,(21)(22)(23)(24) and even cognition (V59M) (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of oral sulfonylurea in improving glycemic control of diabetic patients due to KCNJ11 mutations after transfer from insulin therapy has been confi rmed by many reports, with doses ranging from 0.05 to 1.5 mg/kg/d (12)(13)(14)(15)(16)(17); however data concerning the use of sulfonylurea in the treatment of PNDM with DEND syndrome have shown variable results. Several mutations related to severe DEND syndrome (Q52R, G53R, V59G, I296L, G334D) are insensitive to glibenclamide (4,12,19,20); nevertheless in some forms of intermediate DEND syndrome (I167L, G53D, H46L, V59M), characterized by less severe developmental delay and without epilepsy, glibenclamide therapy has improved metabolic control, neuromuscular symptoms (17,(21)(22)(23)(24) and even cognition (V59M) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations related to severe DEND syndrome (Q52R, G53R, V59G, I296L, G334D) are insensitive to glibenclamide (4,12,19,20); nevertheless in some forms of intermediate DEND syndrome (I167L, G53D, H46L, V59M), characterized by less severe developmental delay and without epilepsy, glibenclamide therapy has improved metabolic control, neuromuscular symptoms (17,(21)(22)(23)(24) and even cognition (V59M) (25). Evidence that sulfonylurea could change CNS blood fl ow and function was provided by the use of Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, insulin secretion from β-V59M islets was stimulated by tolbutamide; this is expected because the drug bypasses the metabolic steps and blocks K ATP channels directly (31), thereby triggering membrane depolarization and insulin secretion. Although V59M K ATP channels are blocked less potently by sulfonylureas, this is still sufficient to elicit secretion in β-V59M mice and in human patients (32). In vivo, the lower insulin content and reduced β cell number of β-V59M islets are also expected to contribute to the hypoinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the CNS symptoms, this would depend on the ability of sulphonylureas to cross the blood-brain barrier (BBB). Although it is not clear to what extent sulphonylureas can cross BBB, early studies of iDEND patients treated with sulphonylureas suggested that sulphonylurea drugs can indeed treat CNS symptoms [57,62,63].…”
Section: Implications For Therapymentioning
confidence: 99%